Differentiation and academic control over policy in Central and Eastern Europe: The case of Romania. (September 2017) - Proteasa, Viorel; Andreescu, Liviu; Curaj, Adrian
This article adds a political perspective to the phenomenon of higher education de-differentiation, by building on Gary Rhoades' neo-institutionalist account. Diversity is operationalized on a hallmark dimension for Central and Eastern Europe: the public–private divide. Higher education is conceived of as a structured organizational field and its institutionalization in Central and Eastern Europe is surveyed in a comparative approach, focusing on the institutions governing the competition for (tuition paying) students and the normative images of higher education (accreditation, quality assurance, classifications and rankings). Critical junctures are identified in regard to the structuration and re-structuration of higher education in Romania, and the agency of the ministers is traced in relation to their academic background. The article builds on evidence from studies of system-level diversity or differentiation in higher education, the structuration of higher education as an organizational field, and the more recent empirical accounts on the impact of the agency of academics in policy formulation in Central and Eastern Europe (especially those in office as ministers of education).